Preparation method of anti-scaling cathode with alloy microstructure

By constructing an alloy microstructure and alkali-resistant protective layer on the cathode surface, combined with the design of the inert coating, the automatic peeling of scale crystals and alkali-resistant corrosion resistance are achieved, the cathode scale problem is solved, and the stability and efficiency of electrochemical reactions are improved .

CN119320956AActive Publication Date: 2025-01-17DALIAN UNIV OF TECH

Patent Information

Application Number
CN202411323339.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-17
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prevent cathode scaling, resulting in a hard deposition layer forming on the cathode surface during the electrochemical reaction, affecting the reaction efficiency and equipment life.

Method used

The anti-scale cathode preparation method of alloy microstructure is used to construct the alloy microstructure through electrochemical deposition, and an alkali-resistant protective layer and an inert coating are built on its surface. The automatic dropout of scale crystals is achieved by using H2 bubble migration and vibration, which enhances the electrode Alkaline corrosion resistance and bonding power of inert coating.

Benefits of technology

It realizes automatic peeling of scale crystals and alkali corrosion resistance on the electrode surface, solves the cathode scaling problem, does not require chemical agents or additional operating steps, maintains the continuity and efficiency of electrochemical reactions, and is low-carbon, simple and efficient. Features.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320956A_ABST
    Figure CN119320956A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrode preparation, and discloses a preparation method of an anti-scaling cathode with an alloy microstructure, which comprises the following steps: constructing the alloy microstructure on the surface of a substrate; constructing an alkali-resistant protective layer on the surface of the microstructure; and coating an inert coating on the surface of the material with the microstructure. The cathode can utilize generated H2 microbubbles to migrate along an inert surface and gather into a bubble layer, so that the surface of the cathode is prevented from being in contact with H2O, Ca < 2 + > and HCO3 <->. Therefore, only the top end of the microstructure is used as an anchor point of the scale crystal. After the scale crystals are stacked into a chain shape, the stability between the scale crystals and the anchor points becomes weaker and weaker. And meanwhile, H2 is continuously injected to enable the bubble layer to grow into large bubbles, and the large bubbles escape from the surface of the cathode under the action of buoyancy and break when moving to the liquid level. Vibration generated by bubble breakage causes automatic falling of a scale crystal chain which is unstable and stands on the microstructure. In addition, the service life of the anti-scaling cathode in an alkaline environment is greatly prolonged by an alkali-resistant protective layer formed after the alloy microstructure is self-activated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrodes and relates to a method for preparing an anti-scaling cathode with an alloy microstructure. Background Art

[0002] Electrochemical technology has shown great potential in the field of green energy and environmental protection. This technology can use green energy to produce hydrogen from seawater, extract lithium from salt lakes, and desalinate brackish water without adding chemical agents, which reflects its environmental protection and high efficiency. However, one of the key technical difficulties faced in the application of this technology is cathode scaling. The reason for cathode scaling is that the electrolysis reaction of water causes OH near the cathode surface to - The concentration increases with HCO3 in water - , Ca 2+ Mg 2+ The reaction produces insulating CaCO3 and Mg(OH)2, which precipitate on the cathode surface and gradually accumulate to form a hard deposit layer. Since most real water contains calcium and magnesium ions, such as natural seawater, which contains a large amount of calcium ions (0.4268g / L) and magnesium ions (1.3307g / L), as long as the cathode decomposes water (2H2O+e - →2OH - +H2↑) reaction, there will be scale crystals precipitated on the cathode surface, which makes cathode scaling in the electrochemical reaction process in actual water inevitable. Therefore, the inherent scaling phenomenon is plaguing the application of electrochemical technology in actual water.

[0003] At present, there are few reports on preventing cathode scaling at home and abroad. The reference Direct seawater electrolysis by adjusting the local reaction environment of a catalyst reports the introduction of a Lewis acid layer on the cathode surface to capture OH - Preventing the solution pH from rising prevents the formation of scale crystals in the solution. -The capture on the surface exacerbates the nucleation of scale crystals on the electrode surface. In addition, the phase change membrane reported in the reference A membrane-based seawater electrolyser for hydrogen generation converts seawater into pure water for electrolysis in situ through the mechanism of phase change migration. However, the wetting problem of the hydrophobic phase change membrane seriously restricts the development of this method. In addition, the reference Efficient bubble / precipitate traffic enables stable seawater reduction electrocatalysis at industrial-level current densities constructs a honeycomb 3D cathode to generate a large number of small-sized H2 bubbles to achieve uninterrupted rejection of Mg 2+ and Ca 2+ However, this method uses natural wood to make electrodes, which is difficult to apply on a large scale because natural wood is easy to break during the carbonization process. In addition, the reference Visualization of crystal automatic exfoliation on an anti-scaling cathode with well-ordered hydrophobic microcones discovered the mechanism of automatic shedding of scale crystals using copper nanotips highly dispersed on an inert surface. However, the alkali corrosion of copper causes the nanotips to fall off after 8 hours of use, thereby losing the anti-scaling function, so this electrode lacks practical application value.

[0004] The above methods have made some contributions to the research on cathode anti-scaling, but still have not solved this problem. Obviously, to completely solve this problem, it is necessary to develop a new cathode that can realize the automatic shedding function of scale crystals. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing an anti-scaling cathode having an alloy microstructure.

[0006] The technical solution of the present invention:

[0007] A method for preparing an anti-scaling cathode having an alloy microstructure, the steps are as follows:

[0008] (1) Construction of alloy microstructure: The metal substrate is pretreated first, and then a solution of a mixture of metal salt, crystal surface protectant, buffer and surfactant is used as the electrolyte at a constant temperature of 1-99°C and a current density of 1-200 mA / cm 2 The reaction is carried out for 1-300 min to obtain a material having an alloy microstructure;

[0009] (2) Construction of microstructure alkali-resistant protective layer: The material with alloy microstructure is heated to 1-99°C with OH - A solution with a concentration of 0.05-20 mol / L is used as an electrolyte, and after activation by repeated cyclic voltammetry scanning for 1-50,000 times in a potential range of 1-20 V vs RHE, an alkali corrosion-resistant microstructure is obtained;

[0010] (3) Construction of inert coating: prepare an inert coating containing an inert agent, a dispersant and a binder, apply the inert coating evenly to the alkali corrosion-resistant microstructure, and heat cure it at 50-450° C. for 1-300 min in an inert atmosphere to obtain an anti-scaling cathode with an alloy microstructure.

[0011] In step (1), the metal substrate includes but is not limited to stainless steel, iron, copper, titanium, nickel, etc.

[0012] In step (1), the morphology of the microstructure includes but is not limited to cone, column, flower, needle, etc.

[0013] In step (1), the mass ratio of the metal salt, the crystal surface protecting agent, the buffer and the surfactant is 0.1-50:1-20:0.01-10:0.005-5.

[0014] In step (1), the metal salt includes but is not limited to nickel chloride, nickel sulfate, nickel nitrate, nickel sulfamate, ferrous chloride, ferrous sulfate, cobalt chloride, cobalt sulfate, manganese chloride, manganese sulfate, chromium chloride, chromium nitrate, potassium molybdate, sodium molybdate, copper sulfate, copper chloride, stannous chloride, palladium nitrate, titanyl sulfate, sodium hydroxyplatinate, etc. Crystal surface protective agents include but are not limited to sodium chloride, calcium chloride, ammonium chloride, sodium citrate, sodium dihydrogen phosphate, etc. Buffers include but are not limited to boric acid, potassium hydroxide, etc. Surfactants include but are not limited to sodium dodecyl sulfate, sodium dodecyl sulfonate, etc.

[0015] In step (3), the mass ratio of the inert reagent, the dispersant and the binder is 0.5-50:0.01-10:0.1-50.

[0016] In step (3), the inert reagent includes but is not limited to polytetrafluoroethylene, dodecanethiol, perfluorodecyltrimethoxysilane, etc. The dispersant includes but is not limited to xanthan gum, polyvinyl alcohol butyl ester, etc. The binder includes but is not limited to epoxy resin, polydimethylsiloxane, acrylic resin, etc.

[0017] Beneficial effects of the invention: The invention constructs a method for preparing an anti-scaling cathode that can realize the function of automatic shedding of scale crystals. A method for preparing an alloy microstructure by electrochemical deposition is established, and an inert coating is coated on its surface, so that the microstructure is dispersed on the inert coating. This structure can utilize the generated H2 microbubbles to migrate along the inert surface and gather into a bubble layer, thereby preventing the cathode surface from contacting H2O, Ca 2+ 、HCO3 - contact. This causes the scale crystals to grow only in chains on the smaller active sites. Subsequently, the vibrations generated by the H2 bubbles growing larger and bursting cause the scale crystal chains standing on the active sites to automatically fall off. This process is repeated to achieve a dynamic equilibrium process in which the scale crystals automatically fall off. In addition, self-activation is used to give the microstructure surface a protective layer that is resistant to alkali corrosion, which effectively solves the problem of short life of the microstructure active sites. At the same time, by adjusting the composition of the inert coating, the bonding force between the inert surface and the metal substrate is enhanced, thereby solving the problem of short life of the inert coating. The present invention is expected to solve the technical problems of cathode scaling commonly faced by electrochemical technology in practical applications. It does not require the addition of drugs, the addition of operating steps, or the interruption of electrochemical reactions. It has many advantages such as low carbon, simplicity, and high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a preparation flow chart of the present invention.

[0019] Figure 2 This is a physical picture of an anti-scaling electrode with a nickel, iron and cobalt alloy microstructure.

[0020] Figure 3 This is a scanning electron microscope image of an anti-fouling electrode with a nickel, iron and cobalt alloy microstructure.

[0021] Figure 4 This is a scanning electron microscope image of the microstructure of a nickel, manganese and tin alloy.

[0022] Figure 5 This is a scanning electron microscope image of the microstructure of nickel, copper and chromium alloys.

[0023] Figure 6 This is a scanning electron microscope image of a material surface without microstructure.

[0024] Figure 7 This is a scanning electron microscope image of an anti-scaling electrode with a nickel, iron, and cobalt alloy microstructure after an alkaline resistance test experiment. DETAILED DESCRIPTION

[0025] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.

[0026] Example 1

[0027] A method for preparing an anti-scaling electrode with an alloy microstructure is as follows:

[0028] (1) A 40-mesh commercial nickel mesh was used as the substrate. All solutions in the experiment were prepared with analytical grade chemicals and ultrapure water. Before electrodeposition, the nickel mesh was first cleaned to remove surface contaminants and oxides. Electrodeposition was carried out in a two-electrode electrochemical system. The mass ratio of nickel sulfate, ferrous sulfate, cobalt sulfate, ammonium chloride, boric acid and sodium dodecyl sulfate in the electrodeposition solution was 8:3:3:1:10:0.005. The electrodeposition temperature was 35°C and the current density was 5 mA / cm 2 The electrodeposition was carried out for 300 minutes. After deposition, the sample was removed from the electrolyte, rinsed thoroughly with water and ethanol, and stored in anhydrous ethanol.

[0029] (2) The electrodeposited material was subjected to 50,000 repetitive cyclic voltammetry scan activation at 45° C. in a potential range of 19-20 V vs RHE using a 0.05 mol / L sodium hydroxide aqueous solution as an electrolyte, and then cleaned with water for later use.

[0030] (3) An inert coating with a mass fraction ratio of 0.5:0.01:10 of dodecanethiol, polyvinyl alcohol butyl acetal and epoxy resin was prepared in butyl acetate, and the inert coating was evenly applied to the material containing the alloy microstructure by dipping and pulling, and thermally cured at 50°C for 300 minutes to obtain an anti-scaling electrode. The prepared anti-scaling electrode is shown in Figure 2 , the electrode surface microstructure is shown in Figure 3 .

[0031] Example 2

[0032] (1) A 40-mesh commercial stainless steel mesh was used as the substrate. All solutions in the experiment were prepared with analytical grade chemicals and ultrapure water. Before electrodeposition, the stainless steel mesh was first cleaned to remove surface contaminants and oxides. Electrodeposition was carried out in a two-electrode electrochemical system. The mass ratio of nickel chloride, manganese chloride, stannous chloride, sodium citrate, potassium hydroxide and sodium dodecyl sulfate in the electrodeposition solution was 50:0.1:10:20:0.01:5. The electrodeposition temperature was 99°C and the current density was 200 mA / cm 2 Electrodeposition was performed for 1 minute. After deposition, the sample was removed from the electrolyte, thoroughly rinsed with water and ethanol, and stored in anhydrous ethanol. The obtained nickel, manganese, and tin alloy microstructure scanning electron microscopy images are shown in Figure 2. Figure 4 shown.

[0033] (2) The electrodeposited material was subjected to a cyclic voltammetric activation scan at 99° C. using a 20 mol / L sodium hydroxide aqueous solution as an electrolyte in a potential range of 1-10 V vs RHE, and then cleaned with water for later use.

[0034] (3) An inert coating having a mass fraction ratio of 50:10:0.1 of polytetrafluoroethylene, xanthan gum and polydimethylsiloxane was prepared in water, and the inert coating was evenly applied to the material containing the alloy microstructure by a dipping and pulling method, and then thermally cured at 450°C for 30 minutes to obtain an anti-scaling electrode.

[0035] Example 3

[0036] (1) A 40-mesh commercial titanium mesh was used as the substrate. All solutions in the experiment were prepared with analytical grade chemicals and ultrapure water. Before electrodeposition, the titanium mesh was first cleaned to remove surface contaminants and oxides. Electrodeposition was carried out in a two-electrode electrochemical system. The mass ratio of nickel sulfate, copper sulfate, chromium nitrate, sodium chloride, boric acid and sodium dodecyl sulfate in the electrodeposition solution was 15:15:15:10:3:1. The electrodeposition temperature was 1°C and the current density was 1 mA / cm 2 Electrodeposition was performed for 200 minutes. After deposition, the sample was removed from the electrolyte, thoroughly rinsed with water and ethanol, and stored in anhydrous ethanol. The obtained nickel, copper, and chromium alloy microstructure scanning electron microscopy images are shown in Figure 5 shown.

[0037] (2) The electrodeposited material was subjected to 10,000 cyclic voltammetric scan activation at 1° C. in a potential range of 5-15 V vs RHE using a 15 mol / L sodium hydroxide aqueous solution as an electrolyte, and then cleaned with water for later use.

[0038] (3) An inert coating having a mass fraction ratio of 1:5:50 of perfluorodecyltrimethoxysilane, polyvinyl butyl acetal and polydimethylsiloxane was prepared in n-hexane, and the inert coating was evenly applied to the material containing the alloy microstructure by dip coating, and then thermally cured at 120°C for 60 minutes to obtain an anti-scaling electrode.

[0039] Comparative Example 1

[0040] The current density in step (1) of Example 1 was changed to 300 mA / cm 2 The SEM images of the material microstructure are shown in Figure 2. Figure 6 As shown in Figure 2, the electrodeposition current density is too large, which results in the failure of electrodeposition to form alloy microstructure.

[0041] Comparative Example 2

[0042] The current density in step (1) of Example 1 was changed to 0.5 mA / cm 2 Since the electrodeposition current density is too small, the alloy microstructure cannot be formed by electrodeposition.

[0043] Comparative Example 3

[0044] The sodium hydroxide concentration in step (2) of Example 1 was changed to 25 mol / L. - If the concentration is too high, the microstructure of the alloy deposited on the surface will be etched and destroyed during the reaction.

[0045] Comparative Example 4

[0046] The concentration of sodium hydroxide in step (2) of Example 1 was changed to 0.01 mol / L. - The concentration is too low, resulting in the inability to form an alkali corrosion-resistant protective layer on the surface of the alloy microstructure.

[0047] Comparative Example 5

[0048] The heat treatment temperature in step (3) of Example 2 was changed to 460° C. Since the heat treatment temperature was too high, the inert coating was carbonized and lost its inert effect.

[0049] Comparative Example 6

[0050] The heat treatment temperature in step (3) of Example 2 was changed to 30° C. Since the heat treatment temperature was too low, the inert coating could not adhere to the surface of the alloy microstructure.

[0051] Comparative Example 7

[0052] The cyclic voltammetry scanning potential in step (2) of Example 3 was changed to 0.1-0.9 V vs RHE. Since the cyclic voltammetry scanning potential was too low, the alkali corrosion resistant protective layer on the surface of the alloy microstructure could not be formed.

[0053] Comparative Example 8

[0054] The cyclic voltammetry scanning potential in step (2) of Example 3 was changed to 21-25 V vs RHE. Since the cyclic voltammetry scanning potential was too high, the alloy microstructure was etched and destroyed.

[0055] The electrode alkali resistance test experiment was carried out in an electrochemical reaction tank. The anode and cathode used RuO2-IrO2-TiO2 / Ti mesh and anti-scaling electrode respectively. A 1M potassium hydroxide solution was prepared as the electrolyte. At 1mA / cm 2 The reaction was carried out at a constant current density of 1.50 for 120 h. The microscopic morphology of the electrode surface after the reaction was as follows: Figure 7 shown.

[0056] The electrode anti-scaling experiment was carried out in an electrochemical reaction tank. The anode and cathode used RuO2-IrO2-TiO2 / Ti mesh and anti-scaling electrode respectively. 2+ 、360mg / L HCO3 - The aqueous solution was used as the electrolyte. During the reaction, a DC power supply was applied at 1 mA / cm2 The constant current density and reaction time are 1h. The experimental results are shown in Table 1:

[0057] Table 1. Performance comparison of metal mesh electrode and anti-scaling electrode

[0058]

[0059]

Claims

1. A method for preparing an anti-scaling cathode having an alloy microstructure, characterized in that: Here are the steps: (1) Construction of alloy microstructure: The metal substrate is pretreated first, and then a solution of a mixture of metal salt, crystal surface protectant, buffer and surfactant is used as the electrolyte at a constant temperature of 1-99°C and a current density of 1-200 mA / cm 2 The reaction is carried out for 1-300 min to obtain a material having an alloy microstructure; (2) Construction of microstructure alkali-resistant protective layer: The material with alloy microstructure is heated to 1-99°C with OH - A solution with a concentration of 0.05-20 mol / L is used as an electrolyte, and after activation by repeated cyclic voltammetry scanning for 1-50,000 times in a potential range of 1-20 V vs RHE, an alkali corrosion-resistant microstructure is obtained; (3) Construction of inert coating: prepare an inert coating containing an inert agent, a dispersant and a binder, apply the inert coating evenly to the alkali corrosion-resistant microstructure, and heat cure it at 50-450° C. for 1-300 min in an inert atmosphere to obtain an anti-scaling cathode with an alloy microstructure.

2. The method for preparing an anti-scaling cathode having an alloy microstructure according to claim 1, characterized in that: In step (1), the metal substrate is stainless steel, iron, copper, titanium or nickel.

3. The method for preparing an anti-scaling cathode having an alloy microstructure according to claim 1, characterized in that: In step (1), the morphology of the microstructure is cone-shaped, column-shaped, flower-shaped, or needle-shaped.

4. The method for preparing an anti-scaling cathode having an alloy microstructure according to claim 1, characterized in that: In step (1), the mass ratio of the metal salt, the crystal surface protecting agent, the buffer and the surfactant is 0.1-50:1-20:0.01-10:0.005-5.

5. The method for preparing an anti-scaling cathode having an alloy microstructure according to claim 1, characterized in that: In step (1), the metal salt is nickel chloride, nickel sulfate, nickel nitrate, nickel sulfamate, ferrous chloride, ferrous sulfate, cobalt chloride, cobalt sulfate, manganese chloride, manganese sulfate, chromium chloride, chromium nitrate, potassium molybdate, sodium molybdate, copper sulfate, copper chloride, stannous chloride, palladium nitrate, titanyl sulfate, sodium hydroxyplatinate; the crystal surface protective agent is sodium chloride, calcium chloride, ammonium chloride, sodium citrate, sodium dihydrogen phosphate; the buffer is boric acid and potassium hydroxide; the surfactant is sodium dodecyl sulfate and sodium dodecyl sulfonate.

6. The method for preparing an anti-scaling cathode having an alloy microstructure according to claim 1, characterized in that: In step (3), the mass ratio of the inert reagent, the dispersant and the binder is 0.5-50:0.01-10:0.1-50.

7. The method for preparing an anti-scaling cathode having an alloy microstructure according to claim 1, characterized in that: In step (3), the inert reagents are polytetrafluoroethylene, dodecanethiol, and perfluorodecyltrimethoxysilane; the dispersants are xanthan gum and polyvinyl butyl acetal; and the binders are epoxy resin, polydimethylsiloxane, and acrylic resin.

Citation Information

Patent Citations

  • Polyaniline-modified porous material and application thereof

    CN105727596A

  • Method for preparing polymorphic nano-iron / cobalt oxide by means of cyclic voltammetry

    CN107557805A

  • Preparation method of corrosion-resistant coating on surface of metal material as well as product and application of corrosion-resistant coating

    CN113106515A

  • Method for inhibiting scaling on surface of electrode by inducing liquid-phase nucleation of scaling substances through nanometer and microbubbles

    CN114105320A

  • Porous nickel-molybdenum-cobalt hydrogen evolution electrode and preparation method and application thereof

    CN114318393A

Cited By

  • Self-cleaning electrochemical descaling cathode material and preparation method and application thereof

    CN121292589A